The Effect of Breadfruit Leaves Infusion on Acute Renal Failure Rat model Abstract - Muhamad Risdan Hardani; Herri S. Sastramihardja; Afiatin Afiatin (Althea Medical Journal, 2015)
Background : Empirically, breadfruit (Artocarpus altilis) leaf has been used as traditional medicine for several diseases, such as acute renal failure. This research is aimed at finding the effects of breadfruit leaf infusion on blood creatinine levels in rats to model acute renal failure.Methods : This research is an experimental study, using 30 male wistar rats, weighing 150–250 g, divided into 5 groups. The first group is a negative control and the second group is a positive control. Groups 2–5 were induced with Gentamicine and peroxicam for 7 days, and then groups 3–5 given infusion of breadfruit leaf in different doses for 7 days, and then blood creatinine levels were tested at the 15th day. This data was analyzed using a multiple comparison Dunnett T3 test because this data is not homogenous. This research was done in pharmacology laboratorium universitas padjadjaran from Oktober–November 2012.Result : Bases on average creatinine levels of 0.62, 0.87, 0.98, and 0.87 mg/dL observed for the diffetent groups, it was statistically show that significantly different creatinine levels, differing by 0.038 (p < 0.05) were observed for the control group and the group which was given an infusion of breadfruit leaf.Conclusion : It can be concluded that infusions of breadfruit leaf do have an effects on blood creatinine levels in acute renal failure.Key words : acute renal failure, breadfruit leaf, creatinine  DOI: 10.15850/amj.v2n4.527